Monitoring Caribbean tobacco use: baseline adolescent smoking prevalence and regional disparities - Ian R Hambleton; Selvi M Jeyaseelan; Christina Howitt; Anselm J Hennis (Instituto Nacional de Salud Pública, 2017)
Objective. To provide baseline information on tobacco use among adolescents in the Caribbean for the period before country-level implementation of the Framework Convention on Tobacco Control (WHO-FCTC). Materials and methods. Using Global Youth Tobacco Surveys (GYTS) between 2000 and 2008, we report baseline prevalence, 5-year change, and disparities in tobacco use (ever smoked, currently smoke) among adolescents. Results. The Caribbean prevalence of ever-smoked fell from 33.3 to 29.0% with nine of 14 countries reporting a 5-year decrease, and the prevalence of current smokers fell from 12.1 to 11.7% with eight of 14 countries reporting a 5-year decrease. Between-country disparities in the prevalence of ever smoked decreased, while between-country disparities in currently smoked saw little change. Conclusions. This regional summary of tobacco use provides baseline estimates of adolescent smoking, and cross-country smoking disparities for the period before MPOWER implementation. Subsequent GYTS survey rounds can be used to monitor program success.